CHANGING SCHOOL AFTER THE GLOBAL RECESSION : THE CASE OF LATVIA - Žogla, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Latvia demonstrates common trends with the majority of the countries affected by the recession, as well as some peculiarities in overcoming the impact of the global economic and financial recession on education mainly due to an unbelievable austerity. Education in this country has suffered greatly, and its damage is adequate to the 67% of the budget cuts between 2008 and 2011 (IZM, 2011). The article deals with the school improvement after the recession, recent implementation of innovations to cover the damages and catch up with the ideas of the Next Generation learning, to supply schools with the appropriate curricula and meeting the learners needs for their individual development and ability to find jobs, as well as appropriate for the school transition teachers’ further professional development.